DENE TÁRBIYASÍ GIGIENASÍ PÁNINIŃ JOQARÍ OQÍW ORÍNLARÍNÍŃ MÁMLEKETLIK OQÍW REJESINDEGI TUTQAN ORNÍ HÁM ÁHMIYETI - Utepbergenov, A.K.; Mamutov, P.J. (SCIENCE and SOCIETY, 2022)
Currently, the role of hygiene remains relevant. Without knowledge in the field of hygiene, the requirements for physical culture and sports, the standards for the level of physical activity and the dosage of physical activity, as well as hygiene standards, rules for measures aimed at maintaining the health of athletes and schoolchildren, it is not possible. Hygiene, as a branch of medical science, consists of separate branches: environmental hygiene, food hygiene, hygiene of children and adolescents, occupational health, radiation hygiene, military hygiene, social hygiene, hygiene of physical culture and sports.